COVID-19’s Effects on Macroeconomic Indicators in Ethiopia: Systematic Review of Articles - Denano T (Dove Medical Press, 2023)
Tesfaye Denano Department of Statistics, Wolaita Sodo University, Sodo, EthiopiaCorrespondence: Tesfaye Denano, Tel +251911474613, Email tesfaye.d@wsu.edu.etIntroduction: In the midst of the COVID-19 crisis, it might be difficult to provide the most vulnerable people with access to essential services. The main objective of this article is to lay the foundation for future solutions by collecting the results of previous published articles.Methods: This study used a systematic and integrated method that began by searching relevant literature in professional and generally published journal databases from March 2019- December 2021.Results: According to the results of the review, COVID-19 has had a significant effect on real and forecasted key macroeconomic variables such as economic growth, unemployment, inflation, poverty levels, and fiscal and monetary policy. In addition, this review reflects the sectorial effect of COVID-19 on health, factor productivity, domestic trade, exports, tourism, international aviation, remittances, the education sector, foreign direct investment, and the Ethiopian economy.Conclusion: While appropriate social distance and personal protective equipment strategies exist in all types of markets across the country, the government should take precautions against the recurrence of Covid-19 by disseminating credible information. Finally, fiscal optimization should be seen as a broader intervention in the economy as a whole.Keywords: macroeconomic indicators, effects, COVID-19, pandemics, review